Coastal Morphology Assessment and Coastal Protection - Yamamoto, Yoshimichi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Sediment, which collects in rivers and seas to secure a large amount of aggregate, reduces the supply of earth and sand to coasts. Dams and breakwaters constructed in various places also impede the transportation of earth and sand. Furthermore, the maintenance dredging of dam lakes and waterways will also disrupt the supply of sediment to coasts if the dredged sediment is not released back into the water system. Due to these development activities, coastal erosion has become a serious problem in many beaches around the world. Moreover, due to the excessive industrial activities of human beings, the exacerbation of natural disasters caused by global warming is becoming a real problem. In addition, because great earthquakes with a magnitude of 9 or more have occurred about three times per 100 years at boundaries of the Pacific Crust Plate and the Nazca Crust Plate since 1700, the possibility of losing many lives and assets in the Pacific coastal areas due to a huge tsunami caused by a great earthquake should not be underestimated. Therefore, research into the prevention and mitigation of coastal erosion and coastal disasters is becoming increasingly important. This Special Issue, "Coastal Morphology Assessment and Coastal Protection", consists of five peer-reviewed papers, collected to contribute to the technological progress on the prevention of coastal erosion and coastal disaster resulting from large waves and tsunamis.